2012
DOI: 10.1111/j.1749-6632.2012.06834.x
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation of the nucleus accumbens for the treatment of addiction

Abstract: Despite novel medications and other therapeutic strategies, addiction to psychotropic substances remains one of the most serious public health problems worldwide. In this review, beginning with an introduction of deep brain stimulation (DBS), we highlight the importance of the nucleus accumbens (NAc) in the context of the reward circuitry and addictive behavior. We will provide a short historic overview of other neurosurgical approaches to treat addiction and describe the experimental and preclinical data on D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
81
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 80 publications
(148 reference statements)
0
81
0
5
Order By: Relevance
“…Approximately 80,000 individuals have undergone DBS treatment worldwide, with a reported mortality rate of 0-0.4% (10). The side effects associated with DBS are categorized as acute side effects of surgery and long-term side effects.…”
Section: The Side-effect Of Dbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 80,000 individuals have undergone DBS treatment worldwide, with a reported mortality rate of 0-0.4% (10). The side effects associated with DBS are categorized as acute side effects of surgery and long-term side effects.…”
Section: The Side-effect Of Dbsmentioning
confidence: 99%
“…The first report suggesting that DBS could treat depressive disorder was published in 2005 (9). DBS has been authorized for the treatment of epilepsy and OCD in Europe, and for the treatment of refractory OCD treatment in the USA (10). This approval has increased research and promoted the development of DBS, particularly regarding the mechanisms of vagus nerve stimulation (11).…”
Section: Introductionmentioning
confidence: 99%
“…142 Two of the 5 patients were abstinent for at least 5 years following DBS and the remaining 3 had marked decreases in their alcohol consumption. One patient had a 2-week hypomanic episode that resolved after changes in stimulation settings.…”
Section: Addictionmentioning
confidence: 94%
“…62,63 Medial prefrontal cortex stimulation also appeared effective in animal studies, but no human cases have been reported. 129,142 Neuromodulation of the nucleus accumbens has been shown to be effective and safe in the treatment of refractory addiction in small cohorts of patients. Given the societal burden imposed by addictive disorders, additional work in this area is warranted.…”
Section: Addictionmentioning
confidence: 99%
“…83 Müller et al has gone further to characterize DBS as actually granting "full autonomy" to the patient. 59 The ethical underpinnings of DBS treatment for obesity will be further challenged in the clinical-trial phase. Several key factors must be clarified prior to enrollment, including trial design, informed consent, and a greater discussion on the concept that DBS treatment would be a threat to patient identity.…”
mentioning
confidence: 99%